Influence of age, circadian and homeostatic processes on inhibitory motor control: a Go/Nogo task study. - Patricia Sagaspe; Jacques Taillard; Hélène Amiéva; Arnaud Beck; Olivier Rascol; Jean-François Dartigues; Aurore Capelli; Pierre Philip (PLoS ONE, 2012)
INTRODUCTION: The contribution of circadian system and sleep pressure influences on executive performance as a function of age has never been studied. The aim of our study was to determine the age-related evolution of inhibitory motor control (i.e., ability to suppress a prepotent motor response) and sustained attention under controlled high or low sleep pressure conditions. METHODS: 14 healthy young males (mean age = 23 ± 2.7; 20-29 years) and 11 healthy older males (mean age = 68 ± 1.4; 66-70 years) were recruited. The volunteers were placed for 40 hours in "constant routine". In the "Sleep Deprivation SD" condition, the volunteer was kept awake for 40 hours to obtain a high sleep pressure condition interacting with the circadian process. In the "NAP" condition, the volunteer adopted a short wake/sleep cycle (150/75 min) resulting in a low sleep pressure condition to counteract the homeostatic pressure and investigate the circadian process. Performances were evaluated by a simple reaction time task and a Go/Nogo task repeated every 3H45. RESULTS: In the SD condition, inhibitory motor control (i.e., ability to inhibit an inappropriate response) was impaired by extended wakefulness equally in both age groups (P<.01). Sustained attention (i.e. ability to respond accurately to appropriate stimuli) on the executive task decreased under sleep deprivation in both groups, and even more in young participants (P<.05). In the NAP condition, age did not influence the time course of inhibitory motor control or sustained attention. In the SD and NAP conditions, older participants had a less fluctuating reaction time performance across time of day than young participants (P<.001). CONCLUSION: Aging could be a protective factor against the effects of extended wakefulness especially on sustained attention failures due to an attenuation of sleep pressure with duration of time awake.